MiR-29a-deficiency causes thickening of the basilar membrane and age-related hearing loss by upregulating collagen IV and laminin - Ma, Peng; Wang, Shuli; Geng, Ruishuang; Gong, Yongfeng; Li, Mulan; Xie, Daoli; Dong, Yaning; Zheng, Tihua; Li, Bo; Zhao, Tong; Zheng, Qingyin (Frontiers in Cellular Neuroscience, 2023)
Age-related hearing loss (ARHL) is the most common sensory degenerative disease and can significantly impact the quality of life in elderly people. A previous study using GeneChip miRNA microarray assays showed that the expression of miR-29a changes with age, however, its role in hearing loss is still unclear. In this study, we characterized the cochlear phenotype of miR-29a knockout (miR-29a-/-) mice and found that miR-29a-deficient mice had a rapid progressive elevation of the hearing threshold from 2 to 5 months of age compared with littermate controls as measured by the auditory brainstem response. Stereocilia degeneration, hair cell loss and abnormal stria vascularis were observed in miR-29a-/- mice at 4 months of age. Transcriptome sequencing results showed elevated extracellular matrix (ECM) gene expression in miR-29a-/- mice. Both Gene Ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis revealed that the key differences were closely related to ECM. Further examination with a transmission electron microscope showed thickening of the basilar membrane in the cochlea of miR-29a-/- mice. Five Col4a genes (Col4a1-a5) and two laminin genes (Lamb2 and Lamc1) were validated as miR-29a direct targets by dual luciferase assays and miR-29a inhibition assays with a miR-29a inhibitor. Consistent with the target gene validation results, the expression of these genes was significantly increased in the cochlea of miR-29a-/- mice, as shown by RT-PCR and Western blot. These findings suggest that miR-29a plays an important role in maintaining cochlear structure and function by regulating the expression of collagen and laminin and that the disturbance of its expression could be a cause of progressive hearing loss.